“MENCETAK GENERASI CINTA AL-QURAN DENGAN AKHLAK MULIA DAN BERSAMA MEMBANGUN GENERASI BERILMU DAN BERKARAKTER ISLAMI DI TPA RQ DAR ASRAR TAUHID” - Rohma, Siti (INKAMKU : Journal of Community Service, 2025)
The Community Service (KKN) Recognition activity is a form of student service to the community that not only broadens horizons, but also becomes a means of character building for children. This article aims to describe the implementation of KKN Recognition carried out at TPA RQ Dar Asrar Tauhid, Palembang, with a focus on Al-Quran education and Islamic moral development for children. The results of the activity showed a significant increase in the ability to read and memorize the Al-Quran and the formation of children's character through interactive and fun methods. This study also highlights the challenges faced by students and the strategies used in responding to them. This article concludes that collaboration between students, TPA teachers, and the community is the key to forming a generation that loves the Al-Quran and has noble moral